2006
DOI: 10.1080/10611860600613241
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective effect of transferrin targeted citicoline liposomes

Abstract: The high level of expression of transferrin receptors (Tf-R) on the surface of endothelial cells of the blood-brain-barrier (BBB) had been widely utilized to deliver drugs to the brain. The primary aim of this study was to use transferrin receptor mediated endocytosis as a pathway for the rational development of holo-transferrin coupled liposomes for drug targeting to the brain. Citicoline is a neuroprotective agent used clinically to treat for instance Parkinson disease, stroke, Alzheimer's disease and brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…One study even showed that TfR-targeted liposomes encapsulating plasmid DNA could be administrated to a pregnant mouse, cross the placental barrier and mediate gene expression in the developing brain of the fetus (Cornford et al, 2015). Furthermore, endogenous Tf was tested in several studies as a targeting molecule for liposome transport with a variety of therapeutic effects including improvement after stroke and brain injury (Omori et al, 2003;Suresh Reddy et al, 2006), increased brain uptake of HIV drugs (Prabhakar et al, 2011), tumor size reduction in GBM (Jhaveri et al, 2018;Lakkadwala and J. Singh, 2019;C. Liu et al, 2017;Salzano et al, 2016;Sonali et al, 2016b;Zheng et al, 2015), or general gene knockdown after siRNA delivery into the brain (Cardoso et al, 2010;2008).…”
Section: Liposomesmentioning
confidence: 99%
“…One study even showed that TfR-targeted liposomes encapsulating plasmid DNA could be administrated to a pregnant mouse, cross the placental barrier and mediate gene expression in the developing brain of the fetus (Cornford et al, 2015). Furthermore, endogenous Tf was tested in several studies as a targeting molecule for liposome transport with a variety of therapeutic effects including improvement after stroke and brain injury (Omori et al, 2003;Suresh Reddy et al, 2006), increased brain uptake of HIV drugs (Prabhakar et al, 2011), tumor size reduction in GBM (Jhaveri et al, 2018;Lakkadwala and J. Singh, 2019;C. Liu et al, 2017;Salzano et al, 2016;Sonali et al, 2016b;Zheng et al, 2015), or general gene knockdown after siRNA delivery into the brain (Cardoso et al, 2010;2008).…”
Section: Liposomesmentioning
confidence: 99%
“…Such effect is considerably smaller in endothelial cells. However, free citicoline was found to be less radioprotective in the ovarian adenocarcinoma cells than in the endothelial cells [189]. Carbon nanoparticles also exhibit radioprotective effect.…”
Section: Quantum Dots and Nanoparticles As Radiosensitizers For Camentioning
confidence: 99%
“…Lipids, the main component of the cell membrane and brain tissue, may be an ideal material for the encapsulation of NSCs, which might be used to repair brain damage. In fact, lipids have been widely used as carriers to deliver agents to treat, for instance, stroke, Parkinson’s disease, and Alzheimer’s disease . They have even been used to encapsulate hemoglobin, which reduced the size of the cerebral infarct in the rat .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, lipids have been widely used as carriers to deliver agents to treat, for instance, stroke, Parkinson's disease, and Alzheimer's disease. 46 They have even been used to encapsulate hemoglobin, which reduced the size of the cerebral infarct in the rat. 47 To our A primary goal of this study was to develop a novel lipid microcapsule that would provide structural support for transplanted cells to promote regeneration of the CNS after ischemic stroke.…”
Section: ■ Discussionmentioning
confidence: 99%